Design of a new type of intelligent lamp charging cabinet - HUANG Hesong; WEI Guozhao; LIAO Yubo; ZHANG Renyuan; WEI Lanlei (Gong-kuang zidonghua, 2015)
In view of problems of multi-type of battery cell of miner's lamp and multi-method of charging, an intelligent charging cabinet compatible with variety of miner's lamp was designed. The intelligent charging cabinet can accurately control charging voltage and current of manganese lithium batteries, lithium iron phosphate batteries, nickel metal hydride batteries and lead-acid battery, it also achieves functions of detection and display of the charging status, lamp in position, battery fault, and rapid identification and maintenance of health status of battery.